ESR study of free radicals in polysilazane irradiated by gamma rays. (October 2018) - Zhou, Lulu; Zhao, Chenxuan; Liu, Weihua; Li, Yuna; Li, Yunbo; Shen, Rongfang; Wang, Minglei; Wu, Yonglong; Wang, Mouhua
Abstract: Free radicals trapped in polysilazane (PSZ) induced by γ-ray irradiation in an Ar atmosphere at room temperature and their decay behaviors were investigated via electron spin resonance (ESR). The G value of the whole initial free radicals was calculated to be 1.8 radicals/100 eV. The free radicals trapped in PSZ were rather stable in Ar at room temperature, and their half-life was estimated to be 470 h according to the decay line. However, they decayed rapidly via reactions with oxygen when exposed to air, and their half-life decreased to 4 h. Interestingly, the free radicals could not be eliminated completely even though the temperature was increased up to 200 °C in an Ar atmosphere. Combing with ESR parameters calculation using DFT method, we found that Si-centered radicals were the main products of PSZ after irradiation in Ar at room temperature. Additionally, we proposed the probable conversion reactions of these radicals under different post-treatment conditions. Highlights: Free radicals trapped in polysilazane were mainly attributed to silicone radicals. G value of the overall free radicals was calculated to be 1.8 radicals/100 eV. All kinds of free radicals could decay rapidly via oxidation reactions. The free radicals could not be eliminated completely by annealing for a short time.